2017
DOI: 10.1248/bpb.b16-00598
|View full text |Cite
|
Sign up to set email alerts
|

Anticytotoxin Effects of Amentoflavone to Pneumolysin

Abstract: Pneumolysin (PLY) is a devastating bacterial protein toxin of Streptococcus pneumoniae that punctures the cytomembrane, leading to pathological reactions, such as cell disruption and inflammation. Drugs capable of closely impacting the toxin are considered advantageous in the treatment of bacterial infections. Amentoflavone (AMF) is a chemical substance extracted from traditional Chinese herbs. Previous studies have demonstrated that AMF has multiple pharmacological effects and mentioned without attenuating pn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 23 publications
1
20
0
Order By: Relevance
“…The finding that amentoflavone targets PFO activity was expected since PFO is also a member of the CDC family. Here, our data support the inhibitory effect of amentoflavone on CDC family toxins (Zhao et al, 2017;Shen et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…The finding that amentoflavone targets PFO activity was expected since PFO is also a member of the CDC family. Here, our data support the inhibitory effect of amentoflavone on CDC family toxins (Zhao et al, 2017;Shen et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…To date, there have been numerous studies on the development and use of natural compounds against bacterial infection via targeting toxins and other virulence factors (Qiu et al, 2012;Zhang et al, 2014;Wang et al, 2015). Zhao et al reported the anticytotoxin effects of amentoflavone on pneumolysin, a devastating bacterial protein toxin of Streptococcus pneumoniae and a member of the CDC family (Alouf, 2000;Zhao et al, 2017). Besides, study of Shen et al showed that amentoflavone effectively inhibited suilysin-mediated hemolysis, a member of the CDC family toxin from Streptococcus suis (Shen et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amentoflavone has been shown to have antioxidant (21), anticancer (22), anti-inflammatory (21), antibacterial (23), antiviral (24), and antiradiation (25) activities. In addition, we recently found that amentoflavone exhibits strong antagonizing effects against pneumolysin by interacting with the toxin and reducing the oligomerization of wild-type PLY, suggesting that amentoflavone is an effective antivirulence agent (26). In this study, we investigated the antivirulence and anti-inflammatory activities of amentoflavone and investigated its mechanism of action on S. suis-induced infection.…”
mentioning
confidence: 98%